Modeling financial risk contributes to construction projects; case study of expansion food industries. Issue 1 (31st December 2022) - Gad, Nouran A.; Abdel-Monem, Mohamed; El-Dash, Karim; Abdel-Hamid, Mohamed
ABSTRACT: The allocation of financial risks among project stakeholders is an important decision affecting the project success after the unexpected political and economic changes took place in Egypt and changes from 2011-2016. Some financial risks in a project are uncontrollable and impacted project stakeholders. Therefore, the research focuses on the know -how of applying modelling financial risk management from different perspectives. This paper presents FRAM is a dynamic model to identify and assess financial factors of risks with reference to project stakeholders; an owner/developer, contractor, financial agencies/ banks and project management companies before construction phase takes place using multi analysis tools.